Diagnostic Challenges in Uterine Smooth Muscle Tumors: Distinguishing Cellular Leiomyoma from STUMP in a Reproductive-Age Woman - Hanum, Muhammad Rakha Nabil Abiyyu; Ayuandari, Sarrah; Sianturi, Rifan Morgan Dorema; Ariffianto, Adi; Widad, Shofwal (JURNAL KESEHATAN REPRODUKSI, 2026)
Uterine smooth muscle tumors of uncertain malignant potential (STUMP) are rare uterine neoplasms with histological features between benign leiomyomas and leiomyosarcomas. Their unpredictable biological behavior poses diagnostic and therapeutic challenges, particularly in reproductive-age women where hysterectomy—the conventional definitive treatment—is avoided to preserve fertility. A 35-year-old nulligravida woman presented with prolonged menstrual bleeding and severe dysmenorrhea (VAS 7) for two years. Previous hormonal therapy with dienogest and norethisterone provided partial relief. MRI revealed multiple subtypes 3, 5, and 6 myomas (55 cm3) and an endometriotic cyst. After six months of GnRH agonist therapy with persistent symptoms, laparoscopic myomectomy with adhesiolysis and excision of endometriotic nodules was performed. Five leiomyomas were excised using laparoscopic morcellation, followed by uterine reconstruction. Histopathology showed a cellular tumor composed of spindle to oval cells with mild pleomorphism and 4 mitoses per 10 HPF, without necrosis or hemorrhage—features consistent with cellular leiomyoma, with STUMP as a differential diagnosis. Immunohistochemistry revealed Ki-67 positivity in 3% of cells, supporting cellular leiomyoma. The postoperative course was uneventful, and regular follow-up was scheduled. Differentiating STUMP from cellular leiomyoma is challenging due to overlapping histopathological features. Low proliferative indices such as Ki-67 <5% favor benign behavior. Fertility-preserving management via laparoscopic myomectomy is feasible when performed with contained morcellation to minimize recurrence risk. Reported recurrence rates following conservative management range from 7–21%, with promising fertility outcomes yielding 38–41% pregnancy rates. Long-term surveillance is essential because recurrences and rare malignant transformations may occur several years postoperatively. This case highlights the diagnostic challenge of differentiating cellular leiomyoma from STUMP and underscores the value of combining histopathology and immunohistochemistry in management. Laparoscopic myomectomy offers a fertility-preserving option with a reported 13.2% recurrence rate and 38.8% pregnancy success rate after 24 or more follow-ups. Further case accumulation is essential to refine fertility-preserving protocols for this rare entity.